2021
DOI: 10.1097/md.0000000000027350
|View full text |Cite
|
Sign up to set email alerts
|

The traditional and modifiable risk factors of coronary artery disease – a community-based cross-sectional study among 2 populations

Abstract: A community-based cross-sectional study was undertaken by the Cardiology Society of India (Kerala Chapter) to determine the prevalence of coronary artery disease (CAD) and its risk factors. The periodontal health status of the rural and urban participants in the Thiruvananthapuram district of Kerala was evaluated to document any association between periodontal disease (PD) and CAD and to describe any shared risk factors. The participants were selected using a multistage cluster random sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…These associations have been explained by the presence of environmental and genetic risk factors, as well as by the presence of chronic inflammation [ 103 ]. It has already been reported that periodontal disease can lead to an increased risk of cardiovascular disease of 19%, and there may even be an increased relative risk of up to 44% if patients with periodontitis are over 65 years of age [ 104 ]. Comparative studies have been conducted in patients who have shown a significantly higher prevalence of periodontal disease in patients with COPD compared to healthy individuals [ 101 , 105 ].…”
Section: Periodontal Disease: a Risk Factor Associated With The Devel...mentioning
confidence: 99%
“…These associations have been explained by the presence of environmental and genetic risk factors, as well as by the presence of chronic inflammation [ 103 ]. It has already been reported that periodontal disease can lead to an increased risk of cardiovascular disease of 19%, and there may even be an increased relative risk of up to 44% if patients with periodontitis are over 65 years of age [ 104 ]. Comparative studies have been conducted in patients who have shown a significantly higher prevalence of periodontal disease in patients with COPD compared to healthy individuals [ 101 , 105 ].…”
Section: Periodontal Disease: a Risk Factor Associated With The Devel...mentioning
confidence: 99%
“…The methods of the oral examination and scoring criteria were discussed in detail in an article published previously. [ 21 ] Using standardized techniques, the periodontal health condition of participants from the Thiruvananthapuram district of Kerala’s rural and urban areas was assessed. The periodontal health of the teeth and oral hygiene were evaluated using a modification of the Ramfjord PD index.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The mesial, distal, buccal, and lingual aspects of each indexed tooth were examined, and the highest possible score was noted. [ 21 ] The periodontal condition of the teeth was assessed using a standard periodontal probe graded in millimeters, which gauged the clinical attachment loss by measuring between the tooth’s cementoenamel junction and the bottom of the gingival sulcus. The gingival and periodontal components of the PD index were assessed.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation